MYOSLID Is a Novel Serum Response Factor–Dependent Long Noncoding RNA That Amplifies the Vascular Smooth Muscle Differentiation Program. Issue 10 (October 2016) - Zhao, Jinjing; Zhang, Wei; Lin, Mingyan; Wu, Wen; Jiang, Pengtao; Tou, Emiley; Xue, Min; Richards, Angelene; Jourd'heuil, David; Asif, Arif; Zheng, Deyou; Singer, Harold A.; et al.
Abstract : Objective—: Long noncoding RNAs (lncRNA) represent a growing class of noncoding genes with diverse cellular functions. We previously reported on SENCR, an lncRNA that seems to support the vascular smooth muscle cell (VSMC) contractile phenotype. However, information about the VSMC-specific lncRNAs regulated by myocardin (MYOCD)/serum response factor, the master switch for VSMC differentiation, is unknown. Approach and Results—: To define novel lncRNAs with functions related to VSMC differentiation, we performed RNA sequencing in human coronary artery SMCs that overexpress MYOCD. Several novel lncRNAs showed altered expression with MYOCD overexpression and one, named MYOcardin-induced Smooth muscle LncRNA, Inducer of Differentiation ( MYOSLID ), was activated by MYOCD and selectively expressed in VSMCs. MYOSLID was a direct transcriptional target of both MYOCD/serum response factor and transforming growth factor-β/SMAD pathways. Functional studies revealed that MYOSLID promotes VSMC differentiation and inhibits VSMC proliferation. MYOSLID showed reduced expression in failed human arteriovenous fistula samples compared with healthy veins. Although MYOSLID did not affect gene expression of transcription factors, such as serum response factor and MYOCD, its depletion in VSMCs disrupted actin stress fiber formation and blocked nuclear translocation of MYOCD-related transcription factor A (MKL1). Finally, loss of MYOSLID abrogated transforming growth factor-β1–induced SMAD2 phosphorylation. Conclusions—: We have demonstrated that MYOSLID, the first human VSMC-selective and serum response factor/CArG-dependent lncRNA, is a novel modulator in amplifying the VSMC differentiation program, likely through feed-forward actions of both MKL1 and transforming growth factor-β/SMAD pathways. Abstract : Supplemental Digital Content is available in the text.